Four Degree-of-Freedom Hydrodynamic Maneuvering Model of a Small Azipod-Actuated Ship With Application to Onboard Decision Support Systems - Mathias Marley; Roger Skjetne; Mateusz Gil; Przemyslaw Krata (IEEE Access, 2023)
The main contribution of this paper is a numerical ship motion model of NTNU’s research vessel Gunnerus, capturing the surge, sway, roll, and yaw dynamics when sailing in uniform and steady currents. The model utilizes a crossflow drag formulation for the transverse viscous loads, and it includes a nonlinear formulation for the propulsion and steering loads provided by two azipod thrusters. A wide range of experimental data obtained from sea trials are used for model calibration and validation. The model is intended for development of Decision Support Systems (DSS) that provide the helmsman with recommendations for safe maneuvers. As a demonstration, the model is used to generate input to a previously proposed DSS solution, which uses offline simulations to create a database of the critical navigation area for different encounter scenarios. Additionally, we propose a DSS solution that uses online simulations to predict the future ship trajectory under guidance of a virtual autopilot. The virtual autopilot is designed using a novel hybrid control barrier function formulation to predict the need of evasive maneuvers for collision avoidance.